El efecto volta un fenómeno imprescindible para comprender el funcionamiento interno de una batería - Rodríguez Cruz, William Javier; Garzón Barragán, Isabel (Revista Científica, 2011)
In shaping the future is relevant degree in physics in-depth reflection on the problems of learning and teaching of electromagnetism, in particular how much they understand the fundamentals. Volta effect is a phenomenon that offers the opportunity to understand the inner workings of a battery. Most introductory texts simply state electromagnetism that these devices are sources of electromotive force (emf), which usually takes one hand to take a battery as a black box that is not known what happens in inside it, and moreover, difficult to comprehend the concept of electromotive force and encourages confusion between this concept and the electrical potential difference. This paper explains the Volta effect from two mental experiments and two real experiments. In addition, sets out some elements to take into account to develop a teaching sequence, to introduce the role of batteries in the operation of simple DC circuits, and an explicit differentiation between the concepts of emf and the electrical potential difference.